Implementation of the YouTube Kids Application as a Learning Media to Improve Children's Memorizing of Daily Prayers at RA Al-Fitrah - Yulidar; Yusuf; Ningsih, Yusma; Yusri; Zahrah (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve student learning outcomes in Islamic religious education learning by using the YouTube Kids application. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were kindergarten students. The data for this study were obtained using test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the YouTube Kids application can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 48.71%, the first cycle 67.39% and in the second cycle it increased to 95.96%. Thus, the use of the YouTube Kids application can be used as an alternative to improve student learning outcomes in Islamic religious education learning.